Metabolic control of energetics in human heart and skeletal muscle - Johnson, AW (2012)
Myocardial and skeletal muscle high energy phosphate metabolism is abnormal in heart failure, but the pathophysiology is not understood. Plasma non-esterified fatty acids (NEFA) increase in heart failure due to increased sympathetic drive, and regulate the transcription of mitochondrial uncoupling protein-3 (UCP3), through peroxisome proliferator-activated receptor-α. The aim of the work in this thesis was to determine whether cardiac PCr/ATP ratios and skeletal muscle PCr kinetics during exercise were related to cardiac and skeletal muscle UCP3 levels respectively, thus providing a mechanism for the apparent mitochondrial dysfunction observed in heart failure. Patients having cardiac surgery underwent pre-operative testing, including cardiac and gastrocnemius 31P magnetic resonance spectroscopy. Intra-operatively, ventricular, atrial and skeletal muscle biopsies were taken for measurement of mitochondrial protein levels by immunoblotting, along with mitochondrial function by tissue respiration rates. Fasting plasma NEFA concentrations increased in patients with ventricular dysfunction and with New York Heart Association (NYHA) class. Ventricular UCP3 levels increased and cardiac PCr/ATP decreased with NYHA class, however, demonstrated no relationship to each other. In skeletal muscle, maximal rates of oxidative ATP synthesis (Qmax) related to functional capacity. Skeletal muscle UCP3 levels increased with NYHA class but were unrelated to skeletal muscle Qmax. Tissue respiration experiments revealed no relationship between ventricular function and indices of mitochondrial coupling, furthermore, indices of mitochondrial coupling were unrelated to tissue UCP3 levels. No evidence was found to support mitochondrial uncoupling, mediated through UCP3, as a cause of the abnormalities in cardiac and skeletal muscle high energy phosphate metabolism.